STAKEHOLDERS INVOLVEMENT IN MITIGATING DISASTER PREVALANCE FOR EFFECTIVE DISASTER MANAGEMENT - Al-Fazari, Saeed; Kasim, Narimah (Journal of Surveying, Construction and Property, 2021)
A literature search showed that studies on the categorization and roles of stakeholders engaged in disaster management are still in dearth. This could not be unrelated to the global trend of natural and man-made disasters. The objective of this research is therefore to examine the role played by stakeholders in combating the incidence of disasters in our modern culture. An audit of suitable writing is the method utilized to collect fitting data. The investigation found diverse strategies of categorizing calamity administration partners in past investigate. This investigates, after investigating current writing, distinguished critical partners, counting but not limited to government and its parastatals, NGOs, benefactors, the private segment, media, the scholarly world, territorial collaboration, community / citizen and the prompt environment. Based on the concept of partners, the acceptance that much might be fulfilled within the locale of calamity administration in case all partners are completely recognized, well-coordinated and regarded. In conclusion, this inquires about offers supportive information on the part of partners in relieving the rate of catastrophes to ensure productive administration of fiascos.